2021
DOI: 10.1177/08850666211031494
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Desmopressin in Patients With Intracranial Hemorrhage and a History of Alcohol Use

Abstract: Background: Patients with a history of alcohol use disorder are at an increased risk of hematoma expansion following intracranial hemorrhage (ICH) due to the effects of alcohol on platelet aggregation. Desmopressin (DDAVP) improves platelet aggregation and may decrease hematoma expansion in patients with ICH. However, DDAVP may also increase the risk of hyponatremia and thrombotic events. Evidence is limited regarding the safety and efficacy of DDAVP in alcohol use (AU)-associated ICH. Methods: This was a retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…10–12 One retrospective study reported a decrease in hematoma expansion, but this was limited to the first 24 hours of treatment as the researchers only looked at the first 24 hours as their primary endpoint. 13 A single-center, nonrandomized study of patients with spontaneous ICH on antiplatelet therapy who received combined desmopressin and platelet transfusion had results in line with the PATCH 9 trial: there was no benefit found with early platelet transfusion, and desmopressin failed to decrease hematoma expansion or improve functional outcome. 14 Finally, a meta-analysis of the use of desmopressin to reduce hematoma expansion in antiplatelet-associated ICH found that the literature did not support the routine use of desmopressin for this purpose.…”
Section: Reversal Of Antiplatelet Agentsmentioning
confidence: 90%
See 2 more Smart Citations
“…10–12 One retrospective study reported a decrease in hematoma expansion, but this was limited to the first 24 hours of treatment as the researchers only looked at the first 24 hours as their primary endpoint. 13 A single-center, nonrandomized study of patients with spontaneous ICH on antiplatelet therapy who received combined desmopressin and platelet transfusion had results in line with the PATCH 9 trial: there was no benefit found with early platelet transfusion, and desmopressin failed to decrease hematoma expansion or improve functional outcome. 14 Finally, a meta-analysis of the use of desmopressin to reduce hematoma expansion in antiplatelet-associated ICH found that the literature did not support the routine use of desmopressin for this purpose.…”
Section: Reversal Of Antiplatelet Agentsmentioning
confidence: 90%
“…They found that the incidence of hyponatremia in the DDAVP-treated group was higher, but this number was not statistically significant, and thrombotic complications were likewise similar. 9 The authors concluded that while the use of DDAVP in this population was safe, it did not significantly reduce hematoma expansion.…”
Section: Desmopressinmentioning
confidence: 91%
See 1 more Smart Citation
“…Desmopressin is an analog of the antidiuretic hormone (vasopressin), which is particularly interesting due to its antidiuretic and anticoagulant role. This hormone exerts its anticoagulant activity by increasing the adhesion of platelets to vascular endothelium and vWF multimers, thereby causing the formation of platelet plaques ( 1 , 2 ). The role of desmopressin is well revealed in patients with VWD type 1 who have defects in platelet aggregation due to birth defects or drug side effects ( 3 ).…”
Section: Contextmentioning
confidence: 99%